2020
DOI: 10.31925/farmacia.2020.5.14
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Potential Antiulcerous Action of Hydroalcoholic Extracts From Prunella Vulgaris L. Of Romanian Origin

Abstract: Prunella vulgaris L. (Lamiaceae family) species is widespread throughout the world and the fruit-spike is used in folk medicine in many countries. The Romanian resource of Prunellae spica is poorly studied from a phytochemical and pharmacological point of view; accordingly, the present study aimed to evaluate the anti-ulcer action of a hydroalcoholic extract of this species with standardized polyphenol content. The extracts used were phytochemically characterized by the total polyphenol content (TPC) and by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…It was observed that positive control, methanol fraction and hexane fraction groups all had moderate expressions of mucins in both surface and deep mucosal areas while the negative control group and ethyl acetate group had only mild expressions. This suggests that the plant phytochemicals may have influenced the biosynthesis of mucins which agrees with several published reports on plants with antiulcer activities in which the rats treated with the test extracts showed significantly higher expressions of mucins in the gastric mucosa [47][48][49][50]. The use of immunohistochemical methods in histopathology has become very important in determining tissue markers relevant in drug discovery [51].…”
Section: Effect Of Administration Of Fractions On the Expression Of Pecam-1 In The Gastric Mucosa Of Treated Animalssupporting
confidence: 85%
“…It was observed that positive control, methanol fraction and hexane fraction groups all had moderate expressions of mucins in both surface and deep mucosal areas while the negative control group and ethyl acetate group had only mild expressions. This suggests that the plant phytochemicals may have influenced the biosynthesis of mucins which agrees with several published reports on plants with antiulcer activities in which the rats treated with the test extracts showed significantly higher expressions of mucins in the gastric mucosa [47][48][49][50]. The use of immunohistochemical methods in histopathology has become very important in determining tissue markers relevant in drug discovery [51].…”
Section: Effect Of Administration Of Fractions On the Expression Of Pecam-1 In The Gastric Mucosa Of Treated Animalssupporting
confidence: 85%
“…The results showed that the maximum extraction yield of flavonoids by ultrasonic extraction could be 3.62% using 41% ( v / v ) ethanol as solvent and a liquid to solid ratio of 30:1 (mL/g) for 30.5 min at 79 °C. In addition, the authors carried out ultrasonic extraction of finely ground PV to evaluate its antiulcer [ 40 ] and antitumor [ 41 ] properties. Therefore, Xia et al have presented a new method for PV extraction by using deep eutectic solvents [ 42 ].…”
Section: Extracting Methods Of Pvmentioning
confidence: 99%
“…We conducted quantitative analysis and found that PV contains a fairly large amount of flavonoids in the glycosidic form (hyperoside, rutoside), as well as identified smaller amounts of aglycones (quercetol, kaempferol, apigenin) [ 40 ]. One of the important flavonoids is hyperoside, which alleviates oxidative damage caused by ROS production [ 46 ].…”
Section: Chemical Composition Of Pv Plant Partsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the aqueous extract of PV may mediate the protective effect of gastric ulcers by inhibiting oxidative stress and promoting regenerative processes in the mucosa. Considerable amounts of hyperoside, rutin, isoquercitrin, small amounts of kaempferol, apigenin, and phenolic acids such as caffeic acid are present in the aqueous extract ( Grosan et al, 2020a ). The higher the level of total phenolic content and rosmarinic acid content, the stronger the total antioxidant capacity of PV ( Sarosi et al, 2011 ) ( Supplementary Figure S4 ).…”
Section: Biological Activitiesmentioning
confidence: 99%